Special aspects of hemo-dynamic and reaction of erythrocytes in blood to standard physical load of different qualification female volleyball players - S. L. Popel'; I.G. Tsap; Ya. N. Yatciv; E. Yi. Lapkovsky; A.V. Synitsya; D.V. Pyatnichuk (H.S. Skovoroda Kharkov National Pedagogical University, 2017)
Purpose: to study the aspects of organism's cardio-hemo-dynamic and blood erythrocytes reaction of female volleyball players to standard physical load. Material: with functional methods we studied cardio-hemo-dynamic and with the help of scanning electronic microscopy - erythrocytes' structure in 18 female volleyball players of different qualification (age - 22.0±0.60 years). Results: it was found that maximal physical load causes substantial changes in cardio-hemo-dynamic, which depend on female volleyball players' qualification. These changes have intrinsic to them type of blood circulation system reacting, which is manifested in the following: appropriate changes of some indicators; natural changes of periphery blood erythrocytes. In the article possible mechanisms of realization of female volleyball players' organism's typological features, depending on blood circulation type and erythrocytes' conformation, are discussed. Conclusions: In relaxed state all female volleyball players have non-uniform cardio-hemo-dynamic of blood circulation. With hyper-dynamic blood circulation type, higher indicators of strike and minute blood volume were observed. With hypo-kinetic blood circulation type the opposite picture was observed: indicators of strike and minute blood volume, heart index, load on cardio-vascular system in different periods of day were low.